2016
DOI: 10.1002/14651858.cd012029.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bifeprunox versus placebo for schizophrenia

Abstract: Our results showed some positive effects and a favourable adverse effect profile for bifeprunox, although there were few data overall and none were of high quality. It would seem that these data alone would not have been enough for the FDA to decide to halt progress of the drug to market. We can only assume that we are missing important data. Both the FDA and the relevant pharmaceutical companies have not made all relevant data accessible. As some of these trials also involved an additional haloperidol, olanza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Up until today (28 February 2020), this classification effort has detected new comparisons for review titles, new classes of drugs and new qualifiers from existing RCTs. These discoveries were assessed by Cochrane editors and led to start and, in some cases, accomplishment of at least 14 Cochrane reviews: six on qualifiers (Abbas et al, 2017; Hanafi et al, 2017; Latifeh et al, 2019; Turk, Alkhatib, et al, 2017; Turk, Zuhri Yafi, et al, 2017; Turkmani et al, 2019), one on a class of drugs (Karl et al, 2018) and nine on comparing two drugs (Bazrafshan et al, 2015; Chattopadhyay et al, 2016; Eslami Shahrbabaki et al, 2018; Ibragimov et al, 2019; Mazhari et al, 2017; Nikvarz et al, 2017; Nur & Adams, 2016; Schmidt et al, 2019; Zare & Bazrafshan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Up until today (28 February 2020), this classification effort has detected new comparisons for review titles, new classes of drugs and new qualifiers from existing RCTs. These discoveries were assessed by Cochrane editors and led to start and, in some cases, accomplishment of at least 14 Cochrane reviews: six on qualifiers (Abbas et al, 2017; Hanafi et al, 2017; Latifeh et al, 2019; Turk, Alkhatib, et al, 2017; Turk, Zuhri Yafi, et al, 2017; Turkmani et al, 2019), one on a class of drugs (Karl et al, 2018) and nine on comparing two drugs (Bazrafshan et al, 2015; Chattopadhyay et al, 2016; Eslami Shahrbabaki et al, 2018; Ibragimov et al, 2019; Mazhari et al, 2017; Nikvarz et al, 2017; Nur & Adams, 2016; Schmidt et al, 2019; Zare & Bazrafshan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Bifeprunox, an atypical antipsychotic drug designed for schizophrenia, [129] has completed a phase‐II study in which efficiency and effect in bipolar depression were determined (NCT00245973). Lumateperone in phase‐III clinical studies showed marked improvement with CDSS scores in bipolar depression (NCT03249376) [130] .…”
Section: Piperazine Derivatives In Clinical Trials For Depressionmentioning
confidence: 99%
“…The remaining 5 reviews reported searching websites in the Potential biases section. 26,[55][56][57][58] This was usually a statement that websites were searched for unpublished literature to counteract bias in the published literature.…”
Section: Location Of Details Reportedmentioning
confidence: 99%